2020
DOI: 10.1093/humrep/deaa144
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polycystic ovary syndrome and adverse obstetric and neonatal outcomes: a population study of 9.1 million births

Abstract: Abstract STUDY QUESTION Does polycystic ovary syndrome (PCOS) confer an independent risk for adverse delivery and neonatal outcomes, based on analysis of the Healthcare Cost and Utilization Project-Nationwide Inpatient Sample (HCUP-NIS) database? SUMMARY ANSWER Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…Due to the small number of articles, we relaxed the original inclusion criteria in the protocol (CRD42020182038) and no longer required matched for baseline characteristics. Only studies that met the inclusion criteria were considered 1 : The study design should be RCT 2 ; The participants should be diagnosed as PCOS according to 1990 US NIH criteria, 2003 Rotterdam criteria, or 2006 AE-PCOS criteria without any other aetiologies for hyperandrogenism or infertility 3 ; The study should have a placebo or blank control of PCOS 4 ; The metformin administration should be throughout pregnancy or at least during the first trimester. Studies that did not provide any information on the outcomes of focus were excluded.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small number of articles, we relaxed the original inclusion criteria in the protocol (CRD42020182038) and no longer required matched for baseline characteristics. Only studies that met the inclusion criteria were considered 1 : The study design should be RCT 2 ; The participants should be diagnosed as PCOS according to 1990 US NIH criteria, 2003 Rotterdam criteria, or 2006 AE-PCOS criteria without any other aetiologies for hyperandrogenism or infertility 3 ; The study should have a placebo or blank control of PCOS 4 ; The metformin administration should be throughout pregnancy or at least during the first trimester. Studies that did not provide any information on the outcomes of focus were excluded.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…They suffer from a higher risk of gestational diabetes mellitus (GDM), preterm delivery, pregnancy-induced hypertension (PIH), preeclampsia (PE), miscarriage and increased intrauterine growth restriction (IUGR), extreme birthweight, admission to the neonatal intensive care unit (NICU) for their offspring. 3,4 In addition to reproductive aspects, women with PCOS also exhibit metabolism syndrome features, including insulin resistance (IR), obesity, and dyslipidemia. 1,5 Among these metabolic disorders, IR is most likely a cornerstone of the pathophysiology of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…GWAS have also identified 19 PCOS susceptibility loci among the Han Chinese, European and Korean ancestry [reviewed in detail by McAllister et al (2015) ; Jones and Goodarzi (2016) ; Hiam et al (2019) ]. More so, the fetal origin of PCOS has been studied in human ( Davies et al, 2012 ; Echiburú et al, 2020 ; Mills et al, 2020 ) and animal models including mice ( Sullivan and Moenter 2004 ), rats ( Wu et al, 2010 ), sheep ( Birch et al, 2003 ), and monkeys ( Dumesic et al, 1997 ). The possible fetal predisposition of the syndrome has also been studied further in bovine and human fetal ovaries using qRT-PCR technique ( Hartanti et al, 2020 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between polycystic ovary syndrome and insulin resistance from to : A bibliometric analysis Introduction Polycystic ovary syndrome (PCOS) is a complex disease with highly heterogeneous clinical manifestations, which affects about 6-10% of women of reproductive age worldwide, making them prone to infertility, adverse pregnancy outcomes, endometrial cancer, and other diseases (1,2). Studies have shown that about 35-80% of PCOS patients have insulin resistance (IR) (3,4), which means researchers are paying more and more attention to the role of IR in PCOS.…”
mentioning
confidence: 99%